A Case-Control Study of the Association between Polymorphisms in the Fibrinogen Alpha Chain Gene and Schizophrenia. (19th January 2017) - Rao, Wenwang; Zhou, Na; Zhang, Huiping; Liu, Rui; Zhang, Shangchao; Su, Yingying; Yang, Guang; Ma, Yue; Shi, Jieping; Yu, Yaqin; Yu, Qiong
Abstract : Our previous studies using the mass spectrum analysis provided evidence that fibrinopeptide A (FPA) could be a potential biomarker for schizophrenia diagnosis. We sought further to demonstrate that variants in the fibrinogen alpha chain gene (FGA) coded FPA might confer vulnerability to schizophrenia. 1, 145 patients with schizophrenia and 1, 016 healthy volunteers from the Han population in Northeast China were recruited. The association of three tag single nucleotide polymorphisms (SNPs) (rs2070011 in the 5 ′ UTR, rs2070016 in intron 4, and rs2070022 in the 3 ′ UTR) in FGA and schizophrenia was examined using a case-control study design. Genotypic distributions of these three SNPs were not found to be significantly different between cases and controls (rs2070011: χ 2 = 1.28, P = 0.528 ; rs2070016: χ 2 = 4.11, P = 0.128 ; rs2070022: χ 2 = 1.23, P = 0.541 ). There were also no significant differences in SNP allelic frequencies between cases and controls (all P > 0.05 ). Additionally, the frequency of haplotypes consisting of alleles of these three SNPs was not significantly different between cases and healthy control subjects (global χ 2 = 9.27, P = 0.159 ). Our study did not show a significant association of FGA SNPs with schizophrenia. Future studies may need to test more FGA SNPs in a larger sample to identify those SNPs with a minor or moderate effect on schizophrenia.